Monster blood IV - Stine, R. L. (New York : Scholastic, 1997)
Evan has discovered a new kind of Monster Blood that multiplies into terrifying blue creatures with razor-sharp teeth.
"A Parachute Press book"--T.p. verso.
"An Apple paperback.".
Includes a detachable bookmark and two collectors cards.
4.2
5-8
Keywords: Blood -- Fiction; Horror stories; Monsters -- Fiction; Blood -- Fiction; Horror fiction; Monsters -- Fiction